ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP PERGERAKAN HARGA SAHAM SEKTOR INDUSTRI BARANG KONSUMSI PERIODE 2005-2015 - Mona, Fiona Angela Intania Grace (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to determine the effect of macroeconomic variables, inflation, exchange rate, interest rates and the GDP (Gross Domestic Product) on stock price movements consumer goods industry sector in Indonesia Stock Exchange in 2005-2015.Step-by-step method that is done in this research that classical assumption (normality test, heterocedasticity, multicolinearity test and autocorrelation test), regression analysis, and hypothesis testing (R2 test, F test, T test) by using the program Eviews 6. the study had 132 samples using monthly data from 2005-2015 for each of the study variables.The results of this study show together variabel inflation, the exchange rate, exchange rate and GDP have a significant effect on stock price movements consumer goods industry sector, while partial inflation is negative and not significant to stock price movements consumer goods industry sector, the exchange rate effect negative on stock price movements consumer goods industry sector but significant, exchange rate has positive influence on stock price movements consumer goods industry sector but not significantly, and the GDP is positive and significant impact on stock price movements consumer goods industry sector.Keywords: consumer goods industry sector, macroeconomics, inflation, exchange rates, interest rates, GDP